VINTERGATAN – I. The origins of chemically, kinematically, and structurally distinct discs in a simulated Milky Way-mass galaxy. Issue 4 (14th April 2021) - Agertz, Oscar; Renaud, Florent; Feltzing, Sofia; Read, Justin I; Ryde, Nils; Andersson, Eric P; Rey, Martin P; Bensby, Thomas; Feuillet, Diane K
ABSTRACT: Spectroscopic surveys of the Milky Way's stars have revealed spatial, chemical, and kinematical structures that encode its history. In this work, we study their origins using a cosmological zoom simulation, VINTERGATAN, of a Milky Way-mass disc galaxy. We find that in connection to the last major merger at z ∼ 1.5, cosmological accretion leads to the rapid formation of an outer, metal-poor, low-[α/Fe] gas disc around the inner, metal-rich galaxy containing the old high-[α/Fe] stars. This event leads to a bimodality in [α/Fe] over a range of [Fe/H]. A detailed analysis of how the galaxy evolves since z ∼ 1 is presented. We demonstrate the way in which inside-out growth shapes the radial surface density and metallicity profile and how radial migration preferentially relocates stars from the inner disc to the outer disc. Secular disc heating is found to give rise to increasing velocity dispersions and scale heights with stellar age, which together with disc flaring explains several trends observed in the Milky Way, including shallower radial [Fe/H] profiles above the mid-plane. We show how the galaxy formation scenario imprints non-trivial mappings between structural associations (i.e. thick and thin discs), velocity dispersions, α-enhancements, and ages of stars; e.g. the most metal-poor stars in the low-[α/Fe] sequence are found to have a scale height comparable to old high-[α/Fe] stars. Finally, we illustrate how at low spatial resolution, comparable to the thickness of the galaxy, the proposed pathway to distinct sequences in [α/Fe]–[Fe/H] cannot be captured.